An agile ınformation systems development method in use - AYDIN, Mehmet Nafiz; HARMSEN, Frank; SLOOTEN, Kees van; STEGWEE, Robert A (Elektrik : Turkish journal of electrical engineering & computer sciences, 2004)
Recently, agile information systems development methods, agile methods in short, have got considerable attention from practitioners. One of the reasons seems that agile methods, to some degree, can be adaptable to different project situations. However, little empirical research has been conducted on this subject. The major goal of this research is to identify which aspects of agile methods are perceived as most critical and difficult to realize and how such aspects are adapted in practice. To reach this goal we studied the working practices concerning the adaptation of an agile method in the IT department of one of the leading financial institutes in Europe. We found that especially some principles and techniques of the method needed more care and often required their adaptation. The ways to adapt these aspects in projects provide an empirical ground to discuss the existing theoretical accounts in literature. Such a discussion leads to a number of research questions for future research and provide valuable insights for practitioners.